2019
DOI: 10.1371/journal.pone.0209435
|View full text |Cite
|
Sign up to set email alerts
|

Metformin exhibited anticancer activity by lowering cellular cholesterol content in breast cancer cells

Abstract: Metformin, a widely prescribed anti-diabetic drug, shows anticancer activity in various cancer types. Few studies documented that there was a decreased level of LDL and total cholesterol in blood serum of metformin users. Based on these views, this study aimed to determine if metformin exhibits anticancer activity by alleviating cholesterol level in cancer cells. The present study found that treatment of breast cancer MDA-MB-231 cells with metformin significantly decreased cholesterol content with concomitant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 50 publications
6
63
0
Order By: Relevance
“…Metformin attenuates the systemic biological effect of IR /IGF on tumor promoting signaling by improving insulin sensitivity and suppressing liver glucose output, which leads to reduced levels of systemic circulating insulin [14]. This will further mitigate paracrine signaling, overcome endocrine resistance [51,57] and improve prognosis in breast cancer [58][59][60][61]. The present study supports the hypothesis that adjuvant metformin or other insulinlowering therapeutic interactions may have their largest effect in breast cancer patients with ERpositive T2 tumors.…”
Section: Discussionsupporting
confidence: 82%
“…Metformin attenuates the systemic biological effect of IR /IGF on tumor promoting signaling by improving insulin sensitivity and suppressing liver glucose output, which leads to reduced levels of systemic circulating insulin [14]. This will further mitigate paracrine signaling, overcome endocrine resistance [51,57] and improve prognosis in breast cancer [58][59][60][61]. The present study supports the hypothesis that adjuvant metformin or other insulinlowering therapeutic interactions may have their largest effect in breast cancer patients with ERpositive T2 tumors.…”
Section: Discussionsupporting
confidence: 82%
“…Metformin attenuates the systemic biological effect of IR /IGF on tumor promoting signaling by improving insulin sensitivity and suppressing liver glucose output, which leads to reduced levels of systemic circulating insulin [14]. This will further mitigate paracrine signaling, overcome endocrine resistance [51,57] and improve prognosis in breast cancer [58][59][60][61]. The present study supports the hypothesis that adjuvant metformin or other insulinlowering therapeutic interactions may have their largest effect in breast cancer patients with ERpositive T2 tumors.…”
Section: Discussionsupporting
confidence: 79%
“…We have also shown that in combination, metformin and the statin-mimetic MβCD were synergistic in attenuating cholesterol biosynthesis and cell proliferation [91]. Others have validated our observation that metformin downregulates genes involved in cholesterol biosynthesis, reporting downregulation of HMGCR, LDLR, and SREBP1 [104]. A particularly exciting corollary of these findings is the potential of metformin to synergize with receptor tyrosine kinase inhibitors (RTKIs) against BC.…”
Section: Metformin Action On Cholesterol Egfr Signaling and Lipid Rsupporting
confidence: 60%